A Phi29-based unbiased exponential amplification and genotyping approach improves pathogen detection in tick samples - Zhang, Xi; Chen, Jingjing; Jiang, Pengfei; Xu, Heling; Zhang, Qi; Zhang, Huan; Han, Xiaohu; Chen, Zeliang (Frontiers in Veterinary Science, 2022)
Ticks are vectors for many infectious diseases, such as spotted fever group (SFG) rickettsioses and borreliosis, and are valuable in the study of pathogen ecology. Ticks have several growth stages that vary considerably in size; therefore, in most cases, DNA extracted from ticks is insufficient for subsequent studies, particularly for multiple pathogen screening and genotyping. Unbiased amplification of DNA from tick samples before analysis is a major requirement for subsequent ecological surveys and other studies. Phi29 DNA polymerase, an enzyme that exhibits strand displacement activity, can exponentially amplify DNA randomly, generating large quantities of DNA. In the present study, we developed a Phi29-based unbiased exponential amplification (PEA) assay to obtain sufficient tick DNA for genetic analysis. By using tick-borne pathogen detection and genotyping as a model, we tested and evaluated the feasibility of the assay. DNA was extracted from single ticks and subjected to PEA. The results showed that tick DNA could be amplified up to 105 fold. The amplified products were successfully used for pathogen screening and genotyping. Rickettsia was successfully detected and genotyped in samples with amplified DNA from single ticks. Furthermore, we identified a new genotype of Rickettsia from ticks collected from Dandong city, Liaoning province, Northeast China. This PEA assay is universal and can be extended to other applications where the quantity of DNA is greatly limited.